Addressing Child Marriage in West Sulawesi: The Role of Islamic Institutions in Public Legal Awareness - Nur, Dwi Utami Hudaya; Sadik, M.; Nuzha, Nuzha; Abbas, Ahmad; Ardiansyah, Ardiansyah (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
Child marriage remains a pressing issue in West Sulawesi, where its prevalence is notably high in Indonesia. This study aims to identify the root causes of child marriage and boost legal awareness through the role of Islamic institutions. We also seek to explore the relevance of contingency and power relation theories in understanding the factors contributing to child marriage. This study uses a juridical-sociological approach, integrating primary and secondary data sources. Data collection involved in-depth interviews with key informants, direct observation, and analysis of relevant documents. Two villages in Majene with the highest cases in West Sulawesi were selected. Data triangulation was employed to increase the validity and reliability of the findings. Our finding demonstrates that, based on contingency theory, the root causes of child marriage depend on stigmas rooted in parental attitudes, prevailing social norms, and individual characteristics. Understanding the driving causes of child marriage in West Sulawesi leads this study to propose a conceptual model for action. A wide range of root causes of child marriage calls for a power relation theory that links policy to its implementation. We advocate for collaborative initiatives through the introduction of village regulations and the involvement of Islamic institutions. To further explore this, we invoke the theory of power relations to enhance public awareness. It helps our scheme of collaborative initiatives for enforcing village regulations by connecting law to social norms, enabling people in the village to respect and comply with the rules.